DEVELOPMENT OF MATHEMATICS INTERACTIVE MULTIMEDIA WITH SCRATCH TO ENHANCE STUDENT'S MATHEMATICS UNDERSTANDING ABILITY - Ratu Sarah Fauziah Iskandar; Bambang Avip Priatna Martadiputra; Nurjanah Nurjanah (FKIP Universitas Muhammadiyah Tangerang, 2023)
Interactive media is something that is important to be developed in order to improve students' mathematical understanding abilities. One of the learning media used is scratch. Scratch-assisted learning media on rank numbers material is made to make it easier for students to understand concepts and to increase student interest in learning, by studying it is expected to be able to give birth to creative students in making learning media based on scratch animation. The research design used in this research is the research design of 4D model development (Four D Models). This includes 4 stages, namely the definition, design, development and dissemination stages, which the researcher then simplifies by changing from four stages (4D) to three stages (3D), namely: defining, designing and developing.